Valorização dos sesquiterpenóides ß-cariofileno e óxido de cariofileno por meio da reação de hidroformilação catalisada por complexos de ródio - Amanda de Camargo Faria (2017)
Rhodium catalyzed hydroformylation is a convenient method for the synthesis of compounds with properties that make them potentially applicable in fragrances and pharmaceuticals. The hydroformylation of ß -caryophyllene and caryophyllene oxide was studied in the absence and in the presence of PPh 3, (2-tbuPhO) 3P or (2,4-di-tbuPhO) 3P. The following reaction parameters were evaluated: concentration and nature of phosphorous ligands, temperature, gas pressure and solvent. The hydroformylation of ß -caryophyllene showed similar performance in both solvents, toluene and ethanol, with no significant formation of acetals being observed in the latter solvent, contrary to what was expected. The optimized conditions allowed the yields of up 70% for the major aldehyde, which resulted from the endocyclic double bond. Phosphorous ligand must be added for the reaction to occur since the sesquiterpene was resistant to hydroformylation in a non-promoted system. The use of PPh3 was efficient while bulky monophosphites promoted the isomerization of the substrate, decreasing selectivity. Under the conditions studied for the hydromormylation of caryophyllene oxide, active and selective systems were achieved and the major aldehyde was obtained in the yields of up 90%. This substrate was reactive even in a non-promoted system, but the use of bulky monophosphites accelerated the reaction. The use of diethyl carbonate, dimethyl carbonate, 2-methyltetrahydrofuran and p-cimene was found to be a valuble alternative for toluene without the loss of activity and selectivity for the desired products, thus increasing the sustainability of the process.